Genre Features of Jamal Kemal's Epics - Nazarova Dildora (International Journal on Integrated Education, 2021)
An important feature of Jamal Kemal's work is that he appears in our poetry with equal aruz, finger and free genre. The same can be said of his epics. Consequently, the poet's epics are dominated by tradition. In particular, in the "Tosh tug’yon (Stone Rebellion)" on the finger, the national rhyme possibilities are widely used, and in the "Quyosh chashmasi (Fountain of the Sun)" in the aruz, ramal bahri, which is the leader in our ghazals, is created in the form of masnavi.